IDENTITAS DAN INTEGRASI SOSIAL MASYARAKAT DI PESISIR DANAU SIOMBAK KECAMATAN MEDAN MARELAN KOTA MEDAN - Delvi, Latika; Gunawan, Pertiwi; Ayunita, Putri (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
The identity of tralhe people of lake siombak is a multicultural society with various tribes inhabiting the area. The Malay tribe is the majority tribe in Lake Siombak, there are also many other tribes who live in the area as migrant communities such as the Javanese, Batak, Banjar and so on. The aim of this research is to analyze the Lake Siombak community with different identities and discuss community integration in the coastal area of Lake Siombak. Siombak Lake is an area on the coast of Lake Environment 7, Paya Pasir Village, Medan Marelan District, Medan City. The method used in this research uses field research methods with qualitative descriptive data analysis techniques. The results of this research show that a multicultural society with different identities increases harmony in society. The integration that exists between the community is very good, with mutual cooperation and also weekly consultations making the community more integrated. Apart from that, there are many intermarriages found with different tribes.